New data on carabid beetles of Trichotichnus s. str. (Coleoptera: Carabidae) of Yunnan (China) and adjacent areas, with description of six new species and two new subspecies - Kataev, Boris M.; Hongbin, Liang; Wrase, David W. (Zootaxa, 2022)
New data on taxonomy and distribution of several species of ground beetles of the nominotypical subgenus of Trichotichnus Morawitz, 1863 occuring in Yunnan (China) and adjacent areas are provided. Fourteen species are currently recorded from Yunnan. The following new taxa are described: T. (s. str.) angustitarsis sp. n. (western Yunnan, and North West Laos), T. (s. str.) subrobustus sp. n. (northwestern Yunnan), T. (s. str.) schmidti sp. n. (northwestern Yunnan and Nepal), T. (s. str.) fedorenkoi sp. n. (North Vietnam), T. (s. str.) hamulipenis sp. n., with two subspecies: the nominotypical one (northwestern Yunnan) and T. (s. str.) h. nepalensis ssp. n. (Nepal), T. (s. str.) miwai continentalis ssp. n. (southern Sichuan, Yunnan, and North Vietnam), and T. (s. str.) kavanaughi sp. n. (northwesternmost Yunnan). Six species are re-described, with new distributional data. The following species are recorded for the first time: T. (s. str.) doiinthanonensis for China and Vietnam, T. (s. str.) subangulatus for China, and T. (s. str.) fukuharai for the Chinese provinces of Shaanxi and Yunnan. Keys to species similar to T. noctuabundus (the noctuabundus species group) and to Trichotichnus (s. str.) species known from Yunnan are given respectively. Additional justification for the synonymy of T. (s. str.) ellipticus Ito, 2014 [=T. (s. str.) anthracinus Landin, 1955] and T. (s. str.) baehri Ito, 1997 [= T. (s. str.) cyrtops (Tschitschérine, 1906)] is also provided.